Restructuring problems when translating into the mother tongue - Terry Sáenz, Regina (2021)
Restructuring means rewriting the source text in the target language.  It is both a textual operation and a cognitive process that requires proficient transformational skills in the translator’s mother tongue. Any gap between competence and performance or partial access to linguistic knowledge: elocutive idiomatic, and expressive will cause problems during the restructuring process in Spanish. The present study aims to identify, describe, and explain the causes of restructuring problems in translation resulting from the translation student’s mother tongue.